Bridging Indigenous Knowledge and Global English: A Contextual Curriculum Model for Meaningful Learning - Novi Indriyani; Rezky Uspayanti; Dian Agustina Purwanto Wakerkwa (Journal of Education Reseach and Evaluation, 2026)
Nationally standardized English teaching materials in Indonesia often fail to reflect regional linguistic, cultural, and ecological diversity, causing English learning to feel disconnected from students’ lived realities. This study aimed to develop and validate a contextual English curriculum model for senior high schools that integrates indigenous knowledge, multilingual practices, and students’ everyday experiences while remaining aligned with national standards and the Merdeka Curriculum. A research and development design combined with a convergent mixed-methods approach was employed, involving 10 English teachers, 50 students, and 3 expert validators from multiple schools. Data were collected through questionnaires, semi-structured interviews, and expert validation sheets, and analyzed using descriptive statistics, thematic analysis, and Content Validity Index (CVI) procedures. The needs analysis revealed strong demand from teachers and students for culturally grounded materials that foreground local environments and multilingual classroom realities. Based on these findings, a six-unit curriculum was designed incorporating indigenous narratives, community-based themes, and flexible use of local languages to support English learning. Expert validation produced item-level CVI scores ranging from 0.80 to 1.00 and a scale-level average of 0.89, indicating high content validity and cultural appropriateness. The findings demonstrate that culturally and linguistically responsive curriculum design is both feasible and educationally valuable for indigenous and multilingual contexts. The model offers practical guidance for contextualizing English instruction and contributes to broader efforts to promote inclusive and locally grounded language education.